L4-L5-S1 human dermatomes: A clinical, electromyographical, imaging and surgical findings - De Souza Faleiros, Antonio Tadeu [UNESP]; De Lima Resende, Luiz Antonio [UNESP]; Zanini, Marco Antonio [UNESP]; De Lima Castro, Heloisa Amélia; Gabarra, Roberto Colichio [UNESP] (FapUNIFESP (SciELO), 2009)
There is substantial controversy in literature about human dermatomes. We studied L4, L5, and S1 inferior limb dermatomes by comparing clinical signs and symptoms with conduction studies, electromyographical data, neurosurgical findings, and imaging data from computerized tomography (CT) or magnetic resonance imaging (MRI). After analyzing 60 patients, we concluded that L4 is probably located in the medial aspect of the leg, L5 in the lateral aspect of the leg and foot dorsus, and S1 in the posterior aspect of the backside, tight, leg and plantar foot skin. This is the first time that these human dermatomes have been evaluated by combined analysis of clinical, electromyographical, neurosurgical, and imaging data.
Keywords: Eletromyography; Human dermatome; Imaging; Inferior member